Primer tüberkülozun radyolojik tanısında direkt grafi tek başına yeterli midir? - Şimşek, Bige (My University, 2008)
Pulmoner tüberküloz (Tbc) ülkemizde ve dünyada önemli bir morbidite nedeni olarak kalmaya devam etmektedir. Pulmoner tüberküloz şüphesi ile değerlendirilen çocuklarda tanısal güçlükler yaşanmaktadır. Radyolojik konfirmasyon tanıda önemli basamaklardan biridir. Çocuklarda başvurulan ilk radyolojik yöntem halen direkt grafi olmakla birlikte, çoğu kez direkt grafi bulguları güvenilir bulunmamakta ve toraks BT incelemesi de yapılmaktadır. Toraks BT’nin tüberküloz bulgularını ortaya koymaktaki üstünlüğü tartışılmazdır. Ancak hastanın aldığı yüksek radyasyon dozu, yüksek maliyeti ve sedatif ilaçların kullanılmasını gerektirdiği için özellikle çocuklarda seçilmiş olgularda BT’ye başvurulmalıdır. Bu çalışmamızda primer tüberküloz hastalığı tanısı almış olan 24 çocuğun ve tüberküloz şüphesiyle izlenen ancak tüberküloz hastalığı tanısı almayan 30 çocuğun PA akciğer grafilerini ve toraks BT’lerini retrospektif olarak karşılaştırarak, direkt grafinin tek başına yeterli olabileceği bulguları tanımlamayı hedefledik. Sonuçta primer tüberküloz hastalığının en sık başlangıç bulguları olan lenfadenomegali ve/ veya yama tarzı konsolidasyon bulgularının BT’ye gerek duyulmadan direkt grafi ile yüksek doğrulukta ortaya konulabildiğini gördük.

Pulmonary tuberculosis (Tbc) still remains to be an important cause of morbiditiy in the world, and in Turkey, respectively. There are many diagnostic difficulties in the evaluation of the patients with suspected tuberculosis in children. When clinical suspicion of tuberculosis exists, radiological confirmation is one of the most helpful diagnostic investigation. Although it remains to be the first radiological technique in the diagnosis of tuberculosis in children, chest radiography findings are not founded reliable and a thoracal CT is often obtained then. There is no doubt CT is the most efficiant radiologic technique in the evaluation of tuberculosis. But it is an important nottice that there is a high risk because of the high radiation dose and adverse effects of sedatives when CT used in children, and it costs higher than a radiography, so CT must be used only in selected cases. The aim of the study was to determine reliable chest radiography findings can be used significantly in the diagnosis of primary tuberculosis in children alone, comparing with CT. So chest radiographs and thorax tomographies of the 24 children with primary pulmonary tuberculosis and 30 suspected children reviewed. As a result of our study, we see that lymphadenomegaly with/ or patchy paranchymal consolidation, which are the most frequent radiologic findings of primary pulmonary tuberculosis also, can be shown significantly in a chest radiography unless CT obtained.
Keywords: Radyoloji